Myostatin polymorphism in Bali cattle and the gaur - Radzuan, Khairun Nadwa (2016)
Species, gender, breed, nutrition, physical activities and growth promoting agent are among the factors that influence the growth rate of muscles. Genes are one of the contributing factors in muscle development. Myostatin gene (MSTN) is a regulatory gene that has a distinct effect in increasing the number and size of muscle fibre. Mutations of MSTN result in muscle hyperplasia, an increase in number of muscle fibre. Mutation of this gene is responsible for the double muscle trait in cattle. The Bali cattle and gaur are more muscular compared to normal cattle. There may be some forms of mutation present in MSTN in these species which may be similar to the double muscled cattle breeds. The objective of this study was to determine the presence of mutation in MSTN in the highly muscled Bali cattle and gaur which may be responsible for their high muscular trait. The study was carried out (i) to optimise the PCR amplification protocol for MSTN for Bali cattle and the gaur using published protocols for cattle, (ii) to determine the partial nucleotide sequences of MSTN in the Bali cattle and gaur, and (iii) to compare the partial MSTN sequences of the Bali cattle and gaur with those of normal cattle, the Belgian Blue and Piedmontese. DNA were extracted from meat tissue samples of two Bali cattle and faecal samples of two Gaurs. DNA and MgCl2 concentrations as well as PCR amplification protocols were varied to optimise the amplification of three regions of MSTN. The success of PCR amplification was confirmed using agarose gel electrophoresis, and the purified PCR products sequenced. Although successful PCR amplification was achieved for two of the regions (MSTN 1 and MSTN 2), sequence data was obtained only for MSTN 1. The results showed 15 single nucleotide polymorphisms (SNPs) in MSTN 1 of one Bali cattle (Bali 1) when compared to cattle (Bos taurus). The base substitutions were 4885T>A, 5024T>A, 4889G>C, 4888-4890T>G, 4908G>T and 4947A>C. Three insertions were found: 4887_4888insC, 5172_5173insA and 5173insA. Six deletions were observed: 4896delA, 4906delA, 5168delA, 4900delT, 4917delT and 4898delG. In Bali 2 there were substitutions (4890A>G, 4891T>G, 4891T>G), 4949T>A), insertion (5172_5173insC) and deletions (4889delG, 4898delG). In MSTN 1 of Gaur 1 three insertions occurred (4867insC, 4871insC, 5172insC). In addition to five single base deletions (4865delT, 4873delT, 4874delT, 4907delT, 4928delA), there was a 28 bp deletion (4876_4903del). MSTN 1 lof gaur 2 had a deletion of 24 bp (4880_4923del), and six single base deletions (4865delT, 4968delT, 4970delT, 4873delT, 4874delT, 4869delG). The presence of SNPs in MSTN of Bali cattle and the gaur suggests that their muscular nature may be related to the mutations in this gene. However, further study has to be done using more animals.